Size focusing of nanoparticles by thermodynamic control through ligand interactions. Molecular clusters compared with nanoparticles of metals - Jose, Deepa; Matthiesen, John E.; Parsons, Christopher; Sorensen, Christopher M.; Klabunde, Kenneth J. (My University, 2012)
Ligand capped metal entities come in two sizes; (1) molecular clusters of 10 – 200 metal atoms, and (2) nanoparticles of 2000 – 10000 metal atoms. In numerous cases, certain “magic sizes” have been found to be most accessible and stable; clusters of 25, 38, 55, 102 atoms and nanoparticles of 3500 – 5000 atoms or 4 – 5 nm. The most familiar and studied system is that of gold (metal) and thiol (ligand). Herein the methods of synthesis of these gold clusters vs gold nanoparticles are carefully compared. In the cluster case, an important intermediate is (Au[superscript +] ˉSR)[subscript n] polymer, which is not the case in the synthesis of nanoparticles either from metal (vapor) atoms or metal ions. Also, it is shown that thiol can act as both a reductant (Au[superscript 3+] Au[superscript 1+]), and as an oxidant (Au[superscript 0] Au[superscript 1+]). The thermodynamic forces responsible for the favored formation of certain size clusters, and nanoparticles are discussed.
Keywords: Nanoparticles; Thermodynamic control; Ligands; Molecular clusters